Problem of Production of Shale Gas in Germany - N. K. Meden (Vestnik MGIMO-Universiteta)
A bstract: Our magazine publishes a series of articles on shale gas in different countries. This article is about Germany, a main importer of Russian natural gas, so a perspective of exploitation of local shale gas resources is of a clear practical importance for Russia. We discuss external and internal factors which determine position of the German government concerning the shale gas excavation: policy of the USA and the EU, positions of German political parties, influence of the lobbying communities and civic associations. The article contains rich information on vast variety of interests of actors in the domestic discussion. Taking into account the importance of civil society for political decisions, the author rests upon public relations of big companies, their methodic and results. The article summarizes data on reserve estimation and current geological projects, as well all the officially published reports concerning environmental threats cased by fracking technology. On the base of the above analyze, the author predicts possible evolution of the federal government policy.